Konsep Industrialisasi Pada Teori Porter Suplay Chain, RBC, dan Swot - Bramantara, Ezar Nafis; Oktaviatul R., Dhaful; Yasin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
SWOT analysis is an important strategic planning tool that RBC managers can use to conduct a situational analysis of the company. This is a useful technique to evaluate the Strengths (S), Weaknesses (W), Opportunities (O) & Threats (T) that RBC currently faces in its current business environment. RBC is one of the leading organizations in the industry. RBC maintains its dominant position in the market by carefully analyzing and reviewing SWOT analysis. SWOT analysis is a highly interactive process and requires effective coordination between various departments in a company such as – marketing, finance, operations, management information systems, and strategic planning. The SWOT Analysis framework allows organizations to identify internal strategic factors such as - strengths and weaknesses, & external strategic factors such as - opportunities and threats. This leads to the 2X2 matrix – also known as the SWOT Matrix.